Introductory statistics - Weiss, Neil A. (Always learning.)
Summary: Statistically Significant Weiss's Introductory Statistics, Tenth Edition, is the ideal textbook for introductory statistics classes that emphasize statistical reasoning and critical thinking. Comprehensive in its coverage, Weiss's meticulous style offers careful, detailed explanations to ease the learning process. With more than 1,000 data sets and over 3,000 exercises, this text takes a data-driven approach that encourages students to apply their knowledge and develop statistical understanding. This text contains parallel presentation of critical-value and p-value approaches to hypothesis t.